Where Did Young Workers Go? The Increase of Youth NEET in Indonesia During Pandemic - Putranto, FX Gugus Febri; Pratomo, Devanto Shasta; Pudjihardjo, M. (UI Scholars Hub, 2024)
The transition of young workers to youth Not in Employment, Education, and Training (NEET) is part of the problems of employment and welfare of the Indonesian population during the COVID-19 pandemic. Using the 2019 and 2020 National Labor Force Survey (Sakernas) data, this study aims to explain the characteristics and determinants of young workers transitioning to unemployed and inactive NEET compared to remaining employed using multinomial logistic regression, in all and gender model. Most of the young workers who are transitioning into youth NEET are concentrated in Java. Gender, education, digitalization, internet, skills, employment status, and business fields significantly affect the transition of young workers to unemployed and inactive youth NEET. In addition, minimum wages and GRDP, also affect the transition to NEET. Specifically, transition to youth NEET in males are influenced by regional labor market conditions, while females are more influenced by demographic factors and human capital. This research implies the urgency of an education and training investment policy that focuses on digitalization for young workers. Furthermore, COVID-19 gives important lessons about the flexibility of the labor market for young people and the importance of gender-specific employment policies as well as ease of access in human capital investment for female.